2009
DOI: 10.1021/ol901803d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Stapled β3-Peptides through Ring-Closing Metathesis

Abstract: The first synthesis of carbon-stapled beta(3)-peptides is reported. The precursor beta(3)-peptides, with O-allyl beta-serines located in an i/i+3 relationship, were prepared on solid phase. We show that efficient ring-closing metathesis (RCM) of these new beta(3)-peptides proceeds smoothly either in solution or on an appropriate solid support. All products were generated with high selectivity for the E-isomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…This analysis, supported by recent work of Perlmutter42 and Seebach44 suggested that a 21-atom bridge could be accommodated between most i and i + 3 positions of a 14-helix. To test this prediction, we synthesized an analog of β-peptide 2 7 containing (O-allyl)-β 3 -L-Ser at positions 3 and 6 ( 2(3-6) , Figure 1), and subjected it to on-resin ring-closing metathesis using bis(tricyclohexylphosphine)benzylidene ruthenium (IV) dichloride34 to generate 2(3-6)s 45.…”
supporting
confidence: 63%
“…This analysis, supported by recent work of Perlmutter42 and Seebach44 suggested that a 21-atom bridge could be accommodated between most i and i + 3 positions of a 14-helix. To test this prediction, we synthesized an analog of β-peptide 2 7 containing (O-allyl)-β 3 -L-Ser at positions 3 and 6 ( 2(3-6) , Figure 1), and subjected it to on-resin ring-closing metathesis using bis(tricyclohexylphosphine)benzylidene ruthenium (IV) dichloride34 to generate 2(3-6)s 45.…”
supporting
confidence: 63%
“…A wealth of knowledge derived from computational 114,115 and experimental 47,116118 approaches has illuminated the minimal constraints necessary for achieving RCM on peptides using first- and second-generation or Grubbs–Hoveyda ruthenium catalysts. 119,120 An unmet challenge in the synthesis of stapled peptides has been the ability to control olefin geometry in the product, as the use of noncyclometalated ruthenium catalysts typically gives rise to both E and Z isomers that are often inseparable. This imposes challenges for examining the role of olefin geometry in the stability and biological activity of stapled peptides, which, to date, has not been thoroughly explored.…”
Section: Resultsmentioning
confidence: 99%
“…Note added in proof: While the present paper was in print, an independent synthesis of hydrocarbonchain-tethered b 3 -peptides by P. Perlmutter and his group was published [26]. For structural assignment, a couple of 3 14 -helix-typical NOEs and CD-intensity comparisons were used.…”
mentioning
confidence: 99%